Impact of Dependent Coverage Provision of the Affordable Care Act on Insurance Continuity for Adolescents and Young Adults With Cancer. Issue 6 (June 2021) - Winestone, Lena E.; Hochman, Lauren L.; Sharpe, James E.; Alvarez, Elysia; Becker, Laura; Chow, Eric J.; Reiter, Joseph G.; Ginsberg, Jill P.; Silber, Jeffrey H.
Abstract : PURPOSE: The 2010 Dependent Coverage Provision (DCP) of the Affordable Care Act (ACA) allowed enrollees to remain on their parents' health insurance until 26 years of age. We compared rates of insurance disenrollment among patients with cancer who were DCP-eligible at age 19 to those who were not eligible at age 19. METHODS: Using OptumLabs Data Warehouse, which contains longitudinal, real-world, de-identified administrative claims for commercial enrollees, we examined patients born between 1982 and 1993 and diagnosed with cancer between 2000 and 2015. In the recent cohort, patients who turned 19 in 2010-2012 (DCP-eligible to stay on parents' insurance) were matched to patients who turned 19 in 2007-2009 (not DCP-eligible when turning 19). In an earlier control cohort, patients who turned 19 between 2004 and 2006 (not DCP-eligible) were matched to patients who turned 19 between 2001 and 2003 (not DCP-eligible). Patients were matched on cancer type, diagnosis date, demographics, and treatment characteristics. The time to loss of coverage was estimated using Cox models. Difference-in-difference between the recent and earlier cohorts was also evaluated. RESULTS: A total of 2, 829 patients who turned 19 years of age in 2010-2012 were matched to patients who turned 19 in 2007-2009. Median time to disenrollment was 26 months for younger patients versus 22 months for older patients (hazard ratio [HR], 0.85; 95% CI, 0.80 to 0.90; P = .001). In 8, 978 patients who turned 19 between 2001 and 2006, median time to disenrollment was 20 months among both younger and older patients (HR, 0.99; 95% CI, 0.94 to 1.03; P = .59). The difference between the recent cohort and the earlier control cohort was a 15% greater reduction in coverage loss ( P < .0001), favoring those turning 19 after the DCP went into effect. CONCLUSION: In the vulnerable population of adolescent and young adult cancer survivors, the ACA may have lowered the insurance dropout rate.